The Role of Calcitonin Gene Related Peptide (CGRP) in Neurogenic Vasodilation and Its Cardioprotective Effects - Kee, Zizheng; Kodji, Xenia; Brain, Susan D. (Frontiers in Physiology, 2018)
CGRP is a highly potent vasoactive peptide released from sensory nerves, which is now proposed to have protective effects in several cardiovascular diseases. The major α-form is produced from alternate splicing and processing of the calcitonin gene. The CGRP receptor is a complex composed of calcitonin like receptor (CLR) and a single transmembrane protein, RAMP1. CGRP is a potent vasodilator and proposed to have protective effects in several cardiovascular diseases. CGRP has a proven role in migraine and selective antagonists and antibodies are now reaching the clinic for treatment of migraine. These clinical trials with antagonists and antibodies indicate that CGRP does not play an obvious role in the physiological control of human blood pressure. This review discusses the vasodilator and hypotensive effects of CGRP and the role of CGRP in mediating cardioprotective effects in various cardiovascular models and disorders. In models of hypertension, CGRP protects against the onset and progression of hypertensive states by potentially counteracting against the pro-hypertensive systems such as the renin-angiotensin-aldosterone system (RAAS) and the sympathetic system. With regards to its cardioprotective effects in conditions such as heart failure and ischaemia, CGRP-containing nerves innervate throughout cardiac tissue and the vasculature, where evidence shows this peptide to alleviate various aspects of their pathophysiology, including cardiac hypertrophy, reperfusion injury, cardiac inflammation, and apoptosis. Hence, CGRP has been suggested as a cardioprotective, endogenous mediator released under stress to help preserve cardiovascular function. With the recent developments of various CGRP-targeted pharmacotherapy, in the form of CGRP antibodies/antagonists as well as a CGRP analogue, this review provides a summary and a discussion of the most recent basic science and clinical findings, initiating a discussion on the future of CGRP as a novel target in various cardiovascular diseases.